A cultura organizacional do Complexo Hospitalar da UFC: uma análise a partir da implantação da EBSERH - Vasconcelos, Rafael Straus Timbó (2019)
The present work aimed to characterize the organizational culture of the Hospital Complex of the Federal University of Ceará, formed by the Walter Cantídio University Hospital (HUWC) and Assis Chateaubriand Maternity School (MEAC) after adhering EBSERH - Brazilian Company of Hospital Services. Garcia et al. (2015) evidenced that the culture of an organization influences the type of management, concluding that the culture will direct the adopted management style and, consequently, will influence organizational changes. The model used is that of Cameron and Quinn (2011), called Competing Values Framework (CVM), which preconizes four types of organizational culture: hierarchical, clan, innovative and market. The process of joining the Hospital Complex to EBSERH from the perspective of organizational culture was examined, describing how EBSERH was implemented and the impacts on the organizational culture of veteran UFC employees and novice EBSERH employees, as well as pointing out how the four cultural typologies manifests and which one predominates. The research used quantitative and qualitative approaches, being characterized as descriptive, applied nature and using the case study strategy. Interviews were conducted with managers from EBSERH, HUWC, MEAC, and representatives of SINTUFCE. Quantitative data were collected through a survey of the workforce of both hospitals, consisting of UFC servers and EBSERH employees. The results showed that the predominant cultural typology in hospitals, if taken together, is that of clan culture, highlighting that it predominates in MEAC, while in HUWC there was no statistically significant difference between hierarchical and clan typologies, contrary to the first hypothesis. This work hypothesized that hospitals would have a predominantly hierarchical cultural typology. The hypothesis of the clan typology was the dominant one in the healthcare professionals was confirmed; In the administrative area there is a predominance of hierarchical and clan cultures, with no statistically significant difference, rejecting the hypothesis of predominance of market culture in this group. Innovative culture and market culture are minority, both without significant differences between them. The results also indicated that there is no statistically significant differentiation in the cultural typology of UFC servers and EBSERH employees, indicating that - five years after the UFC Hospital Complex adhered to EBSERH - both groups have the same perception of cultural typology. Finally, the qualitative data indicated that the process of adhering to EBSERH was fast and drastic, but did not disrupt the organizational culture typology - the interviewees considered that the five-year period is still too short for a cultural transformation and that it finds in transition process too short for a cultural transformation and that it finds in transition process. The results of this study endorse research on organizational culture in hospital institutions and contribute to the deepening of studies on the phenomenon of the creation of EBSERH and its impacts on the improvement of services offered by SUS.